IMPLEMENTASI E- GOVERNMENT PENGGUNAAN APLIKASI E-BUDDY DALAM PENGELOLAAN SURAT MASUK DI DESA KEPER KECAMATAN KREMBUNG KABUPATEN SIDOARJO - Kurnia Candra Dewi; Ilmi Usrotin Choiriyah (Journal Publicuho, 2025)
This research explores the implementation of the E-Buddy application as a digital administration system in Keper Village, Sidoarjo. The study aims to examine data infrastructure, legal foundation, institutional coordination, human resources, technology support, and leadership strategies in optimising digital correspondence. Data collection was conducted through interviews with village officials and supported by official documents. The findings reveal that E-Buddy significantly improves the efficiency and transparency of administrative services, although challenges remain in internet stability and technical system errors. The study highlights that proper training, backup archiving, and clear coordination mechanisms contribute to the system’s sustainability. The research concludes that E-Buddy plays an essential role in advancing village governance towards digital transformation.